The Influence of Green Marketing Mix on Customer Satisfaction in Apple Inc.’s Sustainable Branding - Farah Rizkya Alessandri (Khazanah Sosial, 2025)
This study aims to examine the impact of the green marketing mix on customer satisfaction, using Apple as a case study of environmentally conscious corporate strategy. The research is driven by the growing consumer demand for sustainable practices and the need to understand which green marketing elements most strongly influence satisfaction and loyalty in the premium technology sector. A quantitative research design was employed, involving the distribution of structured questionnaires to Apple consumers familiar with the company’s environmental initiatives. Data were analyzed using validity testing and multiple regression analysis to assess the contribution of each variable to customer satisfaction. The results indicate that all four elements of the green marketing mix significantly and positively affect customer satisfaction. Notably, green place emerged as the strongest predictor, followed by green price and green promotion. Green product, while the least influential, still had a statistically significant impact. These findings suggest that environmentally conscious retail environments and value-driven pricing strategies play a central role in shaping positive consumer experiences. The implications of this study highlight the strategic importance of integrating sustainability into both marketing communication and physical retail infrastructure. Companies can enhance customer loyalty and brand trust by aligning their green marketing practices with consumers’ environmental values, especially through ethical store design, accessible pricing, and engaging digital promotion. This study contributes original insights by identifying green place as a key determinant of customer satisfaction in the context of sustainable branding. By focusing on the technology sector and employing a robust analytical framework, the research expands the theoretical and practical understanding of green marketing effectiveness in contemporary consumer markets.